Menstrual Hygiene Practices amongst Reproductive Age Group Females Visiting a Tertiary Care Hospital, Lahore - Rozina Shahdat KHAN; Sarah Khalid; Mubeen Saeed; Michelle Gillani (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2024)
Objective: To assess the menstrual hygiene practices in relation to age, educational level, marital status and residence among the females of reproductive age group attending Gynae OPD of LGH.